Intestinal Microbiota in Children With Symptomatic Dientamoeba fragilis Infection: A Case-control Study. Issue 4 (10th November 2020) - van Kalleveen, Michael W.; Budding, Andries E.; Benninga, Marc A.; Savelkoul, Paul H.M.; van Gool, Tom; van Maldeghem, Iris; Dorigo-Zetsma, J. W.; Bart, Aldert; Plötz, Frans B.; de Meij, Tim G.J.
Abstract : Background: Dientamoeba fragilis in children has been associated with gastrointestinal symptoms, like abdominal pain and diarrhea. The mechanism underlying these symptoms in children with D. fragilis remains unclear. We hypothesized that concomitant microbial alterations, which have been described in other parasitic infections, may be associated with gastrointestinal symptoms in D. fragilis . Methods: In this case-control study performed in 2 centers, 19 children referred to a pediatrician because of gastrointestinal symptoms and with a positive fecal PCR for D. fragilis were included as cases. We included 19 healthy children as controls and matched for age and gender, selected from an existing cohort of 63 children. A PCR for D. fragilis was performed on fecal samples of the 19 controls to assess D. fragilis carriership in this asymptomatic group. Microbiota was analyzed with the IS-pro technique, and the intestinal microbiota composition and diversity were compared between the 2 groups. Results: Microbiota of children with D. fragilis and gastrointestinal symptoms did not significantly differ in terms of composition and diversity compared with controls, both on phylum and species level. In the asymptomatic controls, a positive fecal PCR for D. fragilis was found in 16 of 19 (84.2%). Conclusion: Intestinal microbiota does not seem to play a key role in the presence of clinical symptoms in children with D. fragilis . The pathogenicity of D. fragilis and pathophysiologic pathways underlying the development of gastrointestinal symptoms remains yet to be clarified.